2017
DOI: 10.1111/mec.14399
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of a defensive symbiosis, but not endogenous defences, at elevated temperatures

Abstract: Environmental factors, including temperature, can have large effects on species interactions, including mutualisms and antagonisms. Most insect species are infected with heritable bacterial symbionts with many protecting their hosts from natural enemies. However, many symbionts or their products are thermally sensitive; hence, their effectiveness may vary across a range of temperatures. In the pea aphid, Acyrthosiphon pisum, the bacterial symbiont Hamiltonella defensa and its associated APSE bacteriophages con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 87 publications
(151 reference statements)
4
74
0
Order By: Relevance
“…Facultative symbionts in insects can confer conditional fitness benefits to their hosts (Cass et al, 2016;Doremus et al, 2018;Polin et al, 2015), and H. defensa and its APSE-conferred defence against parasitoid wasps is one of the best studied cases (Oliver and Higashi, 2019). The results presented in this study support previous studies reporting a variable toxin cassette across APSE as well as intra-genic recombination.…”
Section: Resultssupporting
confidence: 88%
“…Facultative symbionts in insects can confer conditional fitness benefits to their hosts (Cass et al, 2016;Doremus et al, 2018;Polin et al, 2015), and H. defensa and its APSE-conferred defence against parasitoid wasps is one of the best studied cases (Oliver and Higashi, 2019). The results presented in this study support previous studies reporting a variable toxin cassette across APSE as well as intra-genic recombination.…”
Section: Resultssupporting
confidence: 88%
“…It should be briefly noted that frequent associations between Hamiltonella and X‐type have unclear implications. While European X‐type strains modulate a variety of phenotypes under co‐infection with Spiroplasma (Heyworth & Ferrari, ), examinations of one strain from North America ruled out antiparasitoid defence, rescue of impaired Hamiltonella protection, antifungal defence and thermotolerance (Doremus & Oliver, ; Doremus et al., ), suggesting a need for further study. Also important here—beyond the fact that related strains from a given HFS species may vary in their protective capacities (Łukasik, Guo, et al., )—is that effective protection may require specific combinations of symbiont and enemy genotypes (Cayetano, Rothacher, Simon, & Vorburger, ), and that defence against enemies may be environmentally sensitive (Doremus et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that both aphid and symbiont genotype can govern the efficacy of defence across temperatures. Most consistent, however, was the failure of symbiont defence at moderately warm temperatures frequently encountered in the field (Doremus et al., ). Consistent with these experimental findings, the protective symbionts ( Hamiltonella defensa ) were less common in warm locales across North America.…”
Section: The Stability Of Symbiosis In a Changing Worldmentioning
confidence: 92%